Depot Medroxyprogesterone Acetate, Oral Contraceptive, Intrauterine Device Use, and Fracture Risk. Issue 3 (September 2019) - Raine-Bennett, Tina; Chandra, Malini; Armstrong, Mary Anne; Alexeeff, Stacey; Lo, Joan C.
Abstract : OBJECTIVE: To assess fracture risk among women with depot medroxyprogesterone acetate (DMPA), oral contraceptive pill (OCP), and intrauterine device (IUD) use. METHODS: A retrospective cohort study of 308, 876 women age 12–45 years who initiated DMPA, combined or progestin-only OCPs, and copper and levonorgestrel IUDs from 2005 to 2015. Cumulative DMPA, OCP, and IUD use was assessed. Time since last DMPA injection was quantified as recent (within 2 years) and past (more than 2 years ago). Crude fracture rate was estimated using a Poisson distribution. Unadjusted and adjusted hazard ratios (HRs) were estimated using cox proportional hazards models. RESULTS: Thirteen percent of women used DMPA, 78.6% combined OCPs, 17.4% progestin-only OCPs, and 26.2% IUDs; 29.5% used more than one method. There were 7, 659 fractures in 1, 391, 251 person-years (5.5/1, 000 person-years [95% CI 5.4–5.6]). The fracture rate for women with any DMPA use was 6.6 (95% CI 6.1–7.2) and 7.8 (95% CI 6.0–10.0) for women with recent use and more than 2 years of cumulative use. Women who had recent use with 2 years or less, or more than 2 years of cumulative use had higher fracture risk compared with women who had no DMPA use and used other methods (adjusted HR 1.15 [95% CI 1.01–1.31] and 1.42 [95% CI 1.10–1.83], respectively). Fracture risk was not increased in women with past DMPA use. Women who had more than 2 years cumulative use of combined OCPs and women with any progestin-only OCP use had lower fracture risk compared with women who did not use OCPs and used other methods (adjusted HR 0.85 [95% CI 0.76–0.96] and 0.88 [95% CI 0.80–0.97], respectively). CONCLUSION: Use of DMPA beyond 2 years should not be considered an absolute contraindication. Although DMPA use was associated with slightly increased fracture risk compared with other methods, the absolute risk of fracture was small and was not observed after discontinuation. Abstract : Depot medroxyprogesterone acetate was associated with slightly increased fracture risk compared with other methods; the absolute risk was small and was not observed after discontinuation.